Planar Organization of Multiciliated Ependymal (E1) Cells in the Brain Ventricular Epithelium. Issue 8 (August 2016) - Ohata, Shinya; Alvarez-Buylla, Arturo
Abstract : Cerebrospinal fluid (CSF) continuously flows through the cerebral ventricles, a process essential for brain homeostasis. Multiciliated ependymal (E1) cells line the walls of the ventricles and contribute importantly to CSF flow through ciliary beating. Key to this function is the rotational and translational planar cell polarity (PCP) of E1 cells. Defects in the PCP of E1 cells can result in abnormal CSF accumulation and hydrocephalus. Here, we integrate recent data on the roles of early CSF flow in the embryonic ventricles, PCP regulators (e.g., Vangl2 and Dishevelled), and cytoskeletal networks in the establishment, refinement, and maintenance of E1 cells' PCP. The planar organization mechanisms of E1 cells could explain how CSF flow contributes to brain function and may help in the diagnosis and prevention of hydrocephalus. Trends: Multiciliated ependymal (E1) cells lining the walls of the brain ventricles display location-specific planar cell polarity (PCP) in the orientation and asymmetric positioning of their motile cilia. Defects in the PCP of E1 cells can result in abnormal accumulation of CSF and hydrocephalus. Hydrodynamic forces generated by the flow of CSF might instruct PCP in E1 cells and their embryonic progenitors. PCP regulators and cytoskeletal networks are key for the PCP of E1 cells, both at the single cell and tissue-wide levels.